Early prediction of hypertension during pregnancy in a low-resource setting. Issue 2 (February 2016) - Kumar, Manisha; Gupta, Usha; Bhattacharjee, Jayashree; Singh, Ritu; Singh, Shalini; Goel, Manish; Sharma, Karuna; Rehman, Mujeeb U.
Abstract: Objective: To evaluate the role of maternal factors, biomarkers, and uterine-artery Doppler in the prediction of hypertension during pregnancy. Methods: A prospective cohort study was performed between December 2012 and November 2014. All singleton pregnancies between 11 weeks and 13 weeks, 6 days of pregnancy were included. Patients had their body mass index (BMI, calculated as weight in kilograms divided by the square of height in meters), mean arterial pressure, uterine-artery Doppler pulsatility index, and pregnancy-associated plasma protein A (PAPP-A) and free β-human chorionic gonadotropin levels recorded. Any patients diagnosed with hypertension during follow-up were assigned to the case cohort; all other patients were assigned to the control group. Results: Hypertension during pregnancy was observed in 198 (9.7%) of 2042 patients that attended follow-up. The mean BMI, mean arterial pressure, uterine-artery Doppler pulsatility index, and the PAPP-A level at study enrollment were all significantly correlated with the later development of hypertension ( P  < 0.001 for all variables). The combined sensitivity, specificity, positive predictive value, and negative predictive value of using the investigated parameters to predict hypertension was 76%, 80%, 31%, and 93%, respectively. Conclusion: Patient BMI, mean arterial pressure, PAPP-A, and pulsatility index were found to be effective predictors of hypertension during pregnancy. Combining these predictors may be beneficial in selecting individuals for close monitoring and early intervention during pregnancy.